Effectiveness Tapak Dara Leaf Extract (Catharanthus roseus) Against Corpus Luteum Formation in Mice (Mus musculus) Female - Merta, I Wayan; Kusmiyati, Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research aims to determine the effectiveness of Tapak Dara leaf extract (Catharanthus roseus) to corpus luteum formation in mouse ovaries (Mus musculus) female. This research uses a true experiment and Posttest-Only Control with a quantitative approach. The sample was determined using a random sampling technique with a randomized group design (RAK) research design. The formation of the corpus luteum in the ovaries of mice is known by counting the number of corpus luteum in the mouse ovary incision. The data obtained were analyzed using the one-way ANOVA (Analysis of Variance) test analysis method at a significance level of 5% (α = 0.05), then continued with the Least Significant Difference (BNT) further test at a significance level of 5% (α = 0.05). Hypothesis test results state F Count(3.094) > F table (3.006). So, this research can conclude that Tapak Dara leaf extract (Catharanthus roseus) is significantly effective in the formation of corpus luteum in female mice (Mus musculus).